2010
DOI: 10.1016/j.vetpar.2009.09.048
|View full text |Cite
|
Sign up to set email alerts
|

A wide diversity of zoonotic intestinal parasites infects urban and rural dogs in Neuquén, Patagonia, Argentina

Abstract: The presence of parasites was investigated by the examination of 1944 dog faecal samples collected from urban (n=646) and rural (n=1298) areas of the province of Neuquén, Patagonia, Argentina. Parasitic agents (PA) were found in 37.86% of samples. A total of 15 different PA were detected, including Toxocara canis (16.35%), Taenia spp./Echinococcus spp. (12.65%), Trichurisvulpis (6.06%), Giardia spp. (1.29%), Toxascaris leonina (0.56%), Ancylostomacaninum (0.41%), Dipylidium caninum (0.31%), Diphyllobothrium sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
5
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 10 publications
5
64
5
8
Order By: Relevance
“…In the present study, the high number of dogs found per farm added to the close contact between them and human beings, specially in this region where livestock raising is economically important, generate potential risks of acquiring zoonotic diseases for the rural populations. This finding corroborates results found by Pierangeli et al (2007) and Soriano et al (2010) in the province of Neuquén, Argentina.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the high number of dogs found per farm added to the close contact between them and human beings, specially in this region where livestock raising is economically important, generate potential risks of acquiring zoonotic diseases for the rural populations. This finding corroborates results found by Pierangeli et al (2007) and Soriano et al (2010) in the province of Neuquén, Argentina.…”
Section: Discussionsupporting
confidence: 93%
“…The endoparasite T. vulpis was more prevalent than reported by other studies carried out in rural areas from Nigeria (14.2%) and the Czech Republic (1.7%) (DUBNÁ et al, 2007;UGBOMOIKO et al, 2008). In Argentina, Soriano et al (2010) reported a prevalence of 1.3% in rural areas of Neuquén. Both trichuroid are found in wild animals like foxes, wolves and weasels among others (WEESE; FULFORD, 2011;SANTOS et al, 2012).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Dogs can host several helminth species, many of which are of zoonotic importance and may be a threat to human health causing serious diseases (Soriano et al, 2010;Mateus et al, 2014). In fact, dog parasites represent a potential risk to public health, especially in children or immuno-compromised people, since direct or indirect transmission of parasitic infections from dogs to humans can occur (Martínez-Moreno et al, 2007;Xhaxhiu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…(hookworms), Toxocara canis, Cryptosporidium sp. and Giardia sp., as well as the high impact of these infections in public health 4,9,12,13 . Despite the large number of reports on zoonotic parasites in public parks, beaches and recreational areas, there is a lack of studies about these agents in restricted geographical areas, such as islands.…”
Section: Introductionmentioning
confidence: 99%